1997
DOI: 10.1590/s0103-84781997000200019
|View full text |Cite
|
Sign up to set email alerts
|

Espécies e prevalência das infestações por carrapatos em cães de rua da cidade de Porto Alegre, RS, Brasil

Abstract: O objetivo deste trabalho foi identificar as espécies de carrapatos que parasitam os cães da área urbana de Porto Alegre e conhecer suas prevalências nesta população. Para isso, foram examinados 450 cães de rua de Porto Alegre, colhidos os carrapatos nos animais infestados e estes identificados ao estereomicroscópio por espécie e por estágio. Dentre os animais examinados, 52,44% albergavam carrapatos e destes, 93,22% estavam parasitados por Rhipicephalus sanguineus, 2,97% por Amblyomma aureolatum e 3,81% pelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
4
15
1
12
Order By: Relevance
“…(Acosta 2011). In Porto Alegre, Ribeiro et al (1997) found this species in 93.2% of the infected animals; however their findings differed from those of the present study due to the fact that they analyzed stray animals. Another study found a prevalence of 67.5% among stray dogs in Goiania (Rodrigues et al 2001).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…(Acosta 2011). In Porto Alegre, Ribeiro et al (1997) found this species in 93.2% of the infected animals; however their findings differed from those of the present study due to the fact that they analyzed stray animals. Another study found a prevalence of 67.5% among stray dogs in Goiania (Rodrigues et al 2001).…”
Section: Resultscontrasting
confidence: 99%
“…only (Labruna & Pereira 2001). This result is in agreement with other studies that reported high frequency of this tick in urban areas (Linardi & Nagem 1973, Yamamura & Vidottto 1982, Ribeiro et al 1997, Rodrigues et al 2001, Oyafuso et al 2002, Soares et al 2006.…”
Section: Resultssupporting
confidence: 93%
“…No Brasil, cães de áreas rurais são parasitados principalmente por carrapatos do gênero Amblyomma (MASSARD et al, 1981;O' DWYER et al, 2001) que podem desempenhar papel importante na transmissão do agente para cães e também para seres humanos, enquanto em cães de áreas urbanas, R. sanguineus é o carrapato mais prevalente (MASSARD et al, 1981;RIBEIRO et al, 1997).…”
Section: Discussionunclassified
“…In urban areas, the most frequent tick species is Rhipicephalus sanguineus (RIBEIRO et al, 1997). The absence of adult ticks on the animals of the present study may have been due to the seasonality of this species, since the study was conducted in late fall, a period when R. sanguineus could be in the larval or nymph stages (SOUZA, 2008), living in small cracks in concrete or wood surfaces (DIPEOLU, 1982).…”
Section: Discussionmentioning
confidence: 81%